Role of Customers’ Behavioral Dynamics in Impacting Their Usage Intentions Toward Mobile Banking Channels in UK (Journal of Asian Development Studies, 2025)
This study examines the role of customers’ behavioral dynamics in influencing their intention to use mobile banking channels in the UK. The research focuses on three key independent variables: perceived usefulness, trust in mobile banking security, and peer influence, with usage behavior as the dependent variable. A quantitative, correlational research design was adopted, utilizing a structured questionnaire distributed to 250 respondents via Microsoft Forms. Data analysis using SPSS software revealed that perceived usefulness (β = 0.402, p < 0.01), trust in mobile banking security (β = 0.367, p < 0.01), and peer influence (β = 0.298, p < 0.05) significantly impact mobile banking usage behavior. Findings highlight the importance of security enhancements, user- friendly mobile banking features, and peer recommendations in driving adoption. The study offers practical implications for banks, policymakers, and marketers to improve mobile banking adoption and customer engagement.